Efficient Technology and the Conservation of Natural Forests: Evidence from Sri Lanka - Herath Gunatilake (Asian Development Bank (ADB), 2007)
Existing policy instruments for conserving tropical forests have shown limited success. This paper investigates the feasibility of improving the technical efficiency of the wood processing industry as an alternative approach to forest conservation, using sawmills in Sri Lanka as a case study. Improved wood processing efficiency decreases the volume of raw material (logs) required to produce a given quantity of processed wood products and, therefore, decreases the pressure on natural forests. A stochastic frontier production function was estimated to assess the technical efficiency of sawmilling in Sri Lanka. Given the considerable inefficiency found in sawmilling operations, current sawn wood output can be obtained with 28% less inputs. Compared with other policy measures, technical efficiency improvement has a potential to play a noteworthy role in conserving natural forests. Technological improvements, as a tool for conservation, deserve the attention of researchers and policymakers.
hdl:11540/1863
Keywords: 330; Regenwald; Technische Effizienz; Schätzung; Forstpolitik; Wirkungsanalyse; Sri Lanka